SeMSA: a compact super absorber optimised for broadband, low-frequency noise attenuation - Bennett, Gareth (My University, 2020)
The attenuation of low-frequency broadband noise in a light, small form-factor is an intractable challenge. In this paper, a new technology is presented which employs the highly efficient visco-thermal loss mechanism of a micro-perforated plate (MPP) and successfully lowers its frequency response by combining it with decorated membrane resonators (DMR). Absorption comes from the membranes but primarily from the MPP, as the motion of the two membranes causes a pressure differential across the MPP creating airflow through the perforations. This combination of DMR and MPP has led to the Segmented Membrane Sound Absorber (SeMSA) design, which is extremely effective at low-frequency broadband sound absorption and which can achieve this at deep sub-wavelength thicknesses. The technology is compared to other absorbers to be found in the literature and the SeMSA outperforms them all in either the 20–1000 Hz or 20–1200 Hz range for depths of up to 120 mm. This was verified through analytical, finite element and experimental analyses.
Keywords: Smart & Sustainable Planet; Telecommunications; Aeroacoustics